2022
DOI: 10.31616/asj.2021.0264
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Comparisons among Minimally Invasive Lumbar Interbody Fusion: A Comparison with Three-Way Matching

Abstract: To compare clinical and radiographic outcomes among minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF), extreme lateral lumbar interbody fusion (XLIF), and oblique lateral lumbar interbody fusion (OLIF) techniques. Overview of Literature: To date, there are many reports comparing outcomes between MIS-TLIF and XLIF, MIS-TLIF and OLIF, or XLIF and OLIF procedures. However, there are no previous studies comparing clinical and radiographic outcomes among all these three techniques. Methods: Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
3
11
0
Order By: Relevance
“…Our study found no significant differences between the 2 cohorts in terms of average blood loss and operative time. Our results are consistent with a majority of the studies comparing both single and multilevel fusions that demonstrated no significant differences in perioperative outcomes [8 , 9 , 14 , 37] . These findings may be attributable to the fact that OLIF and XLIF are similar anterolateral techniques that both involve dissection through the retroperitoneal space to gain access to the vertebral disc.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study found no significant differences between the 2 cohorts in terms of average blood loss and operative time. Our results are consistent with a majority of the studies comparing both single and multilevel fusions that demonstrated no significant differences in perioperative outcomes [8 , 9 , 14 , 37] . These findings may be attributable to the fact that OLIF and XLIF are similar anterolateral techniques that both involve dissection through the retroperitoneal space to gain access to the vertebral disc.…”
Section: Discussionsupporting
confidence: 92%
“…[ 35 ] 20 Retrospective L3–L5 45/55 69.0 III XLIF Studies 602 Yingsakmongkol et al. [ 14 ] 30 Retrospective L4–L5 27/73 63.53 III Li et al., 2021 [23] 54 Prospective observational L3–L5 35/65 60.3 II 41 Prospective observational L3–L5 49/51 57.9 II Hiyama et al. [ 27 ] 80 Retrospective L1–L5 60/40 71.6 III Jung et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Correction of sagittal as well as coronal deformities can be achieved using lordotic and big cages [72][73][74][75][76]. Furthermore, LLIF has been demonstrated to restore foraminal height and central canal surface through indirect decompression [76][77][78][79]. However, LLIF has disadvantages, including damage to the psoas, internal organs, or lumbar plexus [72,80].…”
Section: Lateral Lumbar Interbody Fusionmentioning
confidence: 99%
“…TLIF can be performed through a minimally invasive approach using a microscope with a tubular retractor or an endoscope. Compared with PLIF, minimally invasive TLIF can minimize damage to structures that contribute to posterior stability such as interspinous ligaments, contralateral facet joints, and paravertebral muscles [ 21 ].…”
Section: Minimally Invasive Spine Surgery Techniquesmentioning
confidence: 99%